RECYCLING AND CHARACTERIZATION OF SPENT ENGINE OIL USING TWO STAGES: SOLVENT EXTRACTION AND CLAY PERCOLATION TECHNIQUES (FUDMA JOURNAL OF SCIENCES, 2023)
Spent lube oils are continuously generated from factories, vehicles and other machineries.  Most spent engine oil contains harmful substances such as heavy metals and indiscriminate disposal of this oil causes environmental pollution. The recycling of spent engine oil has also become important due to its economic benefits. In this study, solvent extraction and clay percolation techniques were used to recycle spent engine oil. The specific gravity, flash point, viscosity, pour point and total acid number. The specific gravity was 0.8252-0.8937, viscosity at 40oC was from 79.37 to 130.12cSt while at 100oC was 8.50 to 15.64 cSt.  The flash and pour points were 121-214 oC and -14 to -9oC respectively. The total acid number were 5.21 and 2.21 mgKOH/g for untreated oil, 0.43 and 0.315 mgKOH/g for treated oil while the total based number were 8.42 and 6.30 mgKOH/g for the treated oil.  The results suggested that this method can be employed to improve the quality spent engine oil for industrial applications as well as reducing environmental pollution due tospent engine oil.
Keywords: Clay; pollution; properties; solvent extraction; spent engine oil